Intravenous immunoglobulin therapy for severe Clostridium difficile colitis. Issue 3 (1st September 1997) - Salcedo, J; Keates, S; Pothoulakis, C; Warny, M; Castagliuolo, I; LaMont, J T; Kelly, C P
Abstract : Background —Many individuals have serum antibodies against Clostridium difficile toxins. Those with an impaired antitoxin response may be susceptible to recurrent, prolonged, or severe C difficile diarrhoea and colitis. Aims —To examine whether treatment with intravenous immunoglobulin might be effective in patients with severe pseudomembranous colitis unresponsive to standard antimicrobial therapy. Patients —Two patients with pseudomembranous colitis not responding to metronidazole and vancomycin were given normal pooled human immunoglobulin intravenously (200–300 mg/kg). Methods —Antibodies against C difficile toxins were measured in nine immunoglobulin preparations by ELISA and by cytotoxin neutralisation assay. Results —Both patients responded quickly as shown by resolution of diarrhoea, abdominal tenderness, and distension. All immunoglobulin preparations tested contained IgG against C difficile toxins A and B by ELISA and neutralised the cytotoxic activity of C difficile toxins in vitro at IgG concentrations of 0.4–1.6 mg/ml. Conclusion —Passive immunotherapy with intravenous immunoglobulin may be a useful addition to antibiotic therapy for severe, refractory C difficile colitis. IgG antitoxin is present in standard immunoglobulin preparations and C difficile toxin neutralising activity is evident at IgG concentrations which are readily achieved in the serum by intravenous immunoglobulin administration.